Readability of Participant Informed Consent Forms and Informational Documents: From Phase 3 COVID-19 Vaccine Clinical Trials in the United States - Bothun, Luke S. (Mayo Clin Proc, 2021)
OBJECTIVE: To assess the readability of the informed consent forms from the phase 3 COVID-19 vaccine trials conducted in the United States. PATIENTS AND METHODS: English consent forms were used for patients in phase 3 COVID-19 vaccine clinical trials. Consent forms were obtained in October 2020. Using Microsoft Word tools, we analyzed the readability (ie, the ease of reading) of written consent forms and informational documents from phase 3 COVID-19 vaccine clinical trials in the United States from the following manufacturers: AstraZeneca, Moderna, Pfizer, Johnson & Johnson, and Novavax. RESULTS: Owing to low readability and several format factors, this study determined that none of the consent forms or informational documents from the recent phase 3 COVID-19 vaccine clinical trials conducted in the United States met readability standards at the recommended 7th grade readability level for the average vaccine research volunteer in any readability category. The average English-speaking vaccine trial volunteer would have great difficulty comprehending the information provided in the consent forms and informational documents. To ensure that study subjects receive and fully comprehend information regarding a clinical study and can provide reliable consent, greater attention should be given to the development and use of simplified consent forms, multimedia formatting, personal discussion, and comprehension assessments.